Examining the Challenges and Opportunities of Women's Leadership in the Modern Era - Tedjo, Tony (Riviera Publishing, 2024)
Women's leadership in the modern era is still faced with big challenges and complexities, especially related to gender discrimination that still exists in society. However, the modern era also brings opportunities for women to lead in various fields, especially through technological advances and globalization. Women who want to lead must develop the same skills and abilities as men and build strong networks. Women's leadership in the modern era still requires efforts to overcome gender discrimination and increase awareness of the importance of diversity in leadership.